Penerapan Pembelajaran Kooperatif Tipe Think Pair Share pada Mata Pelajaran PPKN untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa di SMK Negeri 4 GOWA - Rachmat, Abdul (Jurnal Paedagogy, 2021)
This study aims to improve student activity and learning outcomes through the application of the think pair share type of cooperative learning at SMK Negeri 4 Gowa. This research method used classroom action research. The subjects of this study were students of class XI TKJ1. The research instrument used observation, tests, and documentation. The data analysis technique used in this research was qualitative and quantitative descriptive analysis. The results of this study indicate that the Think Pair Share type of cooperative learning model can increase activity and learning outcomes. This is evidenced by the increase in student completeness scores from cycle I 41.18% to 85.30% in cycle II and student activity in terms of volunteering to answer questions, working on questions individually, working with group friends increased.